Working Memory Training for Healthy Older Adults: The Role of Individual Characteristics in Explaining Short- and Long-Term Gains - Borella, Erika; Carbone, Elena; Pastore, Massimiliano; De Beni, Rossana; Carretti, Barbara (Frontiers in Human Neuroscience, 2017)
Objective. The aim of the present study was to explore whether individual characteristics such as age, education, vocabulary and baseline performance in a working memory (WM) task --similar to the one used in the training (criterion task)-- predict the short- and long-term specific gains and transfer effects of a verbal WM training for older adults. Method. Four studies that adopted the Borella et al. (2010) verbal WM training procedure were found eligible for our analysis as they included: healthy older adults who attended either the training sessions (WM training group), or alternative activities (active control group); the same measures for assessing specific gains (on the criterion WM task), and transfer effects (nearest on a visuo-spatial WM task, near on short-term memory tasks and far on a measure of fluid intelligence and two inhibitory measures); and a follow-up session. Results. Linear mixed models confirmed the overall efficacy of the training, in the short term at least, and some maintenance effects. In the trained group, the individual characteristics considered were found to contribute (albeit only modestly in some cases) to explaining the effects of the training. Conclusions. Overall, our findings suggest the importance of taking individual characteristics and individual differences into account when examining WM training gains in older adults.